2023
DOI: 10.3126/ijosh.v13i4.53257
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of pesticide use among agricultural workers of Lamatar Village Development Committee, Lalitpur District: A cross-sectional study

Abstract: Introduction: In this fast-developing world, food production has also been changing, making people suffer from various health issues because of pesticide poisoning. Unsafe methods in handling pesticides, especially in middle and low-income countries like Nepal are still practiced, although the deleterious health effects either go unnoticed or are missed or are diagnosed late. Few of the older less costly pesticides remain for years in soil and water although few of them have been banned they are still availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…18 More than half of the farmers use sprayers for powder pesticides on their farms, consistent with a study conducted in Lalitpur Nepal. 19 This study found that the farmers suffered from respiratory problems such as shortness of breath 73(70.9%), cough 60(58.3%), and chest pain 37(35.9%) which was similar to findings from Thailand which revealed that the prevalence of difficulty in breathing and chest pain was significantly higher in farmers than in the controls (OR 2.8, P < 0.01 and OR 2.5, P < 0.05, respectively). 20 This study has showcased the complete use of PPE sets despite showing major health problems such as respiratory and dermal problems, in contrast to the study in Ecuador which suggested very little use of PPE resulting in health problems.…”
Section: Discussionmentioning
confidence: 99%
“…18 More than half of the farmers use sprayers for powder pesticides on their farms, consistent with a study conducted in Lalitpur Nepal. 19 This study found that the farmers suffered from respiratory problems such as shortness of breath 73(70.9%), cough 60(58.3%), and chest pain 37(35.9%) which was similar to findings from Thailand which revealed that the prevalence of difficulty in breathing and chest pain was significantly higher in farmers than in the controls (OR 2.8, P < 0.01 and OR 2.5, P < 0.05, respectively). 20 This study has showcased the complete use of PPE sets despite showing major health problems such as respiratory and dermal problems, in contrast to the study in Ecuador which suggested very little use of PPE resulting in health problems.…”
Section: Discussionmentioning
confidence: 99%